Russian business in the context of the growth of cybercrime: changes in economic behavior and protective mechanisms - S. G. Simonov; I. V. Lysenko (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the identification and analysis of new vectors of cybercrime development, their localization and prevention. The analysis of secondary data, questionnaires, and expert assessment are used as research methods for this problem. The statistics of cybercrime in foreign countries and Russia in recent years have been analyzed. It is found out how the domestic business has changed its attitude to the security of information and information systems of the company. The sectoral landscape of cybercrimes in the Russian Federation for 2023 is presented. New vectors of phishing development are considered in detail and the main resources forged by hackers during phishing attacks are identified. Special attention is paid to phishing by the method of distribution, which today poses the greatest danger to Russian companies. Spoofing has been studied as a new type of cyberattack, where masquerading as a legal object (computer, device or network) is used by hackers as a means of penetrating other computer networks. The characteristics of modern types of spoofing and the negative consequences for business that they lead to are given. The measures taken at the state level to counter new vectors of cybercrime development are indicated. The conclusion is substantiated that state support and information protection measures themselves eliminate the consequences rather than the causes of high cybercrime, which is why the security problem cannot be solved without the participation of domestic business and the population of the country. The consolidated participation of Russian business in the fight against cybercrime is noted, which found its concrete embodiment in the creation of the F.C.C.T. joint-stock company. The key areas of activity of this company in the information technology market and the results of its work in 2023 are highlighted. Attention is focused on the fact that the creation of a joint-stock company F.C.C.T. in the country does not fully solve the problem of ensuring information security, which primarily concerns small and medium-sized business structures. It is stated that many of them, especially in the Russian regions, are not ready to purchase information security services not only financially, but also organizationally. Due to the low demand of entrepreneurs for vulnerability search services in the company’s software, web applications and IT infrastructure, it is proposed to build a typical SOC that meets the most minimal standards for combating cybercrime. An algorithm has been developed to achieve them in the form of step-by-step implementation of simple organizational and methodological recommendations for the prevention of cybercrimes and minimizing their consequences for small and medium-sized businesses.